HUBUNGAN KEBIASAAN MENYIKAT GIGI DENGAN KEJADIAN KARIES GIGI SISWA KELAS IV-V DI SEKOLAH DASAR GMIM TUMPENGAN KABUPATEN MINAHASA - Ni Made Yuliana; Youla Karamoy; I Ketut Harapan; Yenny Liesbeth Siahaan (Poltekkes Kemenkes Medan, 2025)
Dental and oral health maintenance efforts must be carried out early, at elementary school age considering that dental and oral diseases are in the top ten most common diseases and are spread across various regions. The purpose of the study was to determine the relationship between tooth brushing habits and the incidence of dental caries in grades IV - V of GMIM Tumpengan Elementary School, Minahasa Regency. This type of research uses a survey method with a Cross Sectional approach. The time of this research was carried out in the fourth week of May 2024. The location of the study was GMIM Tumpengan Elementary School. The population was 50 people, the sample was the total population, the data obtained were tabulated and analyzed using the chi-square statistical test. This research instrument used a questionnaire including how to brush your teeth and DMF-T examination. The results of the study obtained the distribution of tooth brushing habits with a good category of 36%, less good 64%, caries incidence data with a very low category of 18%, moderate 34%, very high 48%. Based on the chi-square test, the P value is known = (0.000 <0.05). The conclusion is that there is a habit of brushing teeth with the incidence of dental caries in grade IV and V students at GMIM Tumpengan Elementary School.